Cross Breeding Hariana Cattle. Abortions and Secondary Sex Ratio - Tomar, S S; Singh, Narinder (Annals of Arid Zone, 2016)
Hariana cows were bred to Hariana, Brown Swiss, Holsteitl Friesian and Danish Red bulls. Records were analysed for determining the influence of sires on the incidence of abortions and frequency of male and female births. It was observed that: 1, The overall ratio of male to female births in Hariana cows bred to Hariana bulls was higher but this difference was not statistically significant. 2. Breeding of Hariana cows wilh bulls of exotic breeds did not change the sex ratio. 3 The incidence of abortions in Hariana cows bred to Hariana bulls was only 1.1 per cent. 4. The rate of of abortions were higher in cows bred to exotic bulls, as compared to Hariana bulls.